When combinatorial processing results in reconceptualization: toward a new approach of compositionality - Schumacher, Petra B. (Frontiers in Psychology, 2013)
Propositional content is often incomplete but comprehenders appear to adjust meaning and add unarticulated meaning constituents effortlessly. This happens at the propositional level (The baby drank the bottle) but also at the phrasal level (the wooden turtle). In two ERP experiments, combinatorial processing was investigated in container/content alternations and adjective-noun combination transforming an animate entity into a physical object. Experiment 1 revealed that container-for-content alternations (The baby drank the bottle) engendered a Late Positivity on the critical expression and on the subsequent segment, while content-for-container alternations (Chris put the beer on the table) did not exert extra costs. In Experiment 2, adjective-noun combinations (the wooden turtle) also evoked a Late Positivity on the critical noun. First, the Late Positivities are taken to reflect discourse updating demands resulting from reference shift from the original denotation to the contextually appropriate interpretation (e.g., the reconceptualization form animal to physical object). This shift is supported by the linguistic unavailability of the original meaning, exemplified by copredication tests. Second, the data reveal that meaning alternations differ qualitatively. Some alternations involve (cost-free) meaning selection, while others engender processing demands associated with reconceptualization. This dissociation thus calls for a new typology of metonymic shifts that centers around the status of the involved discourse referents.